Coherent nuclear motions in light‐harvesting pigments and dye molecules, probed by ultrafast spectroscopy - Chachisvilis, Mirianas; Fidder, Henk; Pullerits, Tõnu; Sundström, Villy (Journal of Raman Spectroscopy, 1995)
The temporal evolution of the transient absorption response of light‐harvesting antennae and dye molecules was studied. Using 40—90 fs pulses coherent nuclear motions were observed in intact membrane‐bound photosynthetic light‐harvesting pigment‐protein complexes, bacteriochlorophyll α monomer and dye molecules in solutions. Computer simulations based on the harmonic Franck—Condon approximation and the Langevin equation describe qualitatively well the wavelength dependence of the oscillations of the mode when exciting and probing in the blue side of the spectrum.